EARLY STAGE DETECTION OF CARDIOMEGALY: AN EXTENSIVE REVIEW - Debnath Bhattacharyya, Bhanu Prakash Doppala, Divya Midhunchakkaravarthy (International Journal of Advanced Science and Technology, 2019)
Problems related to heart is one of the fundamentally developing issue throughout the globe, prompting a large portion of deaths because of heart issues. The weight of cardiovascular sickness can be enhanced via hazard disease and accordingly essential counteractive action is an imperative need for all engineers of well-being arrangement. For every heart based diseases we need to undergo different medical examinations which kills lot of time to detect the exact root cause, rather than going for several diagnosis mechanisms. In this paper we propose that with limited parameters from the diagnosis results we can identify the issue of Cardiomegaly at early stages.